Systems thinking on the gendered impacts of COVID-19 in Bangladesh: A systematic review - Sarker, Mou Rani; Sarkar, Md. Abdur Rouf; Alam, Mohammad Jahangir; Begum, Ismat Ara; Bhandari, Humnath (Elsevier, 2023)
The COVID-19 pandemic has disproportionately affected women and threatens to overturn four decades of progress in Sustainable Development Goal (SDG) 5: Gender Equality and Women's Empowerment. To better grasp the key areas of concern that gender inequality exists, gender studies and sex-disaggregated evidence are required. Using the PRISMA technique, this review paper is the first attempt to present a comprehensive and current picture of the gendered dimensions of the COVID-19 pandemic in Bangladesh regarding economic well-being, resource endowments, and agency. This study found that women were more likely to face hardship as widows, mothers, or sole breadwinners after the loss of husbands and male household members because of the pandemic. The evidence suggests that the advancement of women during this pandemic was hampered by poor reproductive health outcomes; girls' dropping out of school; job loss; less income; a comparable wage gap; a lack of social security; unpaid work burnout; increased emotional, physical, and sexual abuse; an increase in child marriages; and less participation in leadership and decision-making. Our study found inadequate sex-disaggregated data and gender studies on COVID-19 in Bangladesh. However, our research concludes that policies must account for gender disparities and male and female vulnerability across multiple dimensions to achieve inclusive and effective pandemic prevention and recovery